Anarchism and positivism in Manuel González Prada: Elements to think about the construction of citizenship - Lara-Amat y León, Joan (2020)
In this article we reflect on the contributions of Manuel González Prada to a new citizenship. Although MGP is studied in the literary field, its study in Political Philosophy and Political Thought is important and fundamental. MGP starts from a critique of tradition and, after his trip to Europe and his stay in Barcelona, he will reinforce a renewed criticism based on positivism as a framework of knowledge and on anarchism as a socio-political proposal. This will allow you to analyze the problems of your society through social facts, especially economic inequalities. A prior and necessary criticism for the possibility of building a citizenship.